Development of a Responsive Airbag Hardware Mechanism for Fall Mitigation and Injury Reduction in the Elderly - Sigit Indriyanto; Willy Anugrah Cahyadi; Husneni Mukhtar; Muhammad Fasha Aqillah; Suto Setiyadi (Green Publisher Indonesia, 2026)
Falls pose a significant risk to elderly individuals and often result in serious injuries due to the lack of immediate protective mechanisms. Therefore, a real-time protective system is needed to reduce the impact of falls. The research aims to develop a wearable airbag vest system that integrates real-time fall detection with a servo-based mechanical triggering mechanism for rapid airbag deployment. The system utilized an IMU sensor to monitor body motion and orientation, a microcontroller to process detection logic, and a servo motor to activate a CO₂ inflator through a spherical buckle mechanism. Performance evaluation was conducted to assess IMU accuracy and airbag inflation response. The IMU demonstrated an average orientation error below 2% for yaw, pitch, and roll compared to an inclinometer reference. Inflation tests showed a servo current peak of 1200–2000 mA, with the airbag reaching peak pressure within 1.2–2.5 seconds after triggering, achieving pressure levels between 85 and 120 psi. The proposed servo-based triggering mechanism provides sufficient responsiveness and reliability for wearable fall protection applications.